Silver deposition optimization process on ultrananocrystalline diamond applied to nitrate reduction - Oishi, Silvia Sizuka; Couto, Andrea Boldarini; Botelho, Edson Cocchieri [UNESP]; Ferreira, Neidenei Gomes (Taylor & Francis Ltd, 2019)
Nitrate is a serious contaminant of ground and surface water, which cause high concern in the field of health and environmental protection. In this work, a ternary composite of silver/boron-doped ultrananocrystalline diamond/reticulated vitreous carbon (Ag/B-UNCD/RVC) was prepared and its electrocatalytic activity for nitrate reduction was examined. B-UNCD films were grown by hot filament chemical vapour deposition technique on RVC after a substrate seeding process improvement using 4 nm diamond powder. Compared to conventional 0.25 mu m diamond seeding, this new procedure allowed uniform RVC coverage avoiding its etching process during diamond growth, in addition to obtaining more reproductive electrodes. In order to improve the catalytic effect of B-UNCD/RVC electrodes for nitrate reduction, silver deposition was performed on B-UNCD surface after oxidation for 10, 20 and 30 min in 0.5 mol L-1 H2SO4 solution using a potential of 2 V vs. Ag/AgCl. The most oxidized diamond film (30 min of oxidation) presented the highest silver deposit and particle adhesion. Thus the electrochemical response to nitrate of B-UNCD/RVC oxidized for 30 min was compared to that of RVC and B-UNCD/RVC electrodes showing the important Ag influence in the catalytic process. [GRAPHICS] .
Keywords: Reticulated vitreous carbon; boron-doped ultrananocrystalline diamond; silver; electrodeposition; nitrate